EFEKTIVITAS BELAJAR DI KAFE, PERPUSTAKAAN, DAN KAMAR KOS/RUMAH PADA MAHASISWA TI UBB ANGKATAN 2024: Learning Effectiveness in Cafes, Libraries, and Dorm/Home Rooms among UBB IT Students Class of 2024 - Danuartha, Arjuna; Fadhila, Dafa (Yayasan Al-Amin Qalbu, 2026)
An important factor in determining student academic success is learning effectiveness, currently many students still have difficulty in managing study time due to neglect of their surroundings. Therefore, this study aims to analyze the comparative effectiveness of three alternative study locations (cafes, libraries, and boarding rooms/houses) for UBB Information Technology students of the class of 2024 using a descriptive quantitative approach and Cramer's Rule modeling method to obtain the relative effectiveness weight (w). The results from 31 respondents showed a conflict between student habits and measured effectiveness: although boarding rooms/houses were used most frequently (90.3%), they only ranked second with a negative weight (wz = -4.7), suggesting that high comfort often sacrifices learning effectiveness. Conversely, libraries were rated most effective with the highest positive weight (wy = 13.9), as they were considered most conducive to concentration. Meanwhile, cafes ranked the lowest (wx = -10.8), confirming that external distractions are a major barrier, so this study suggests students prioritize environments that are measured as effective, such as libraries, for tasks that require deep focus.